Population Status Studies and Anthropogenic Impact on Birds of Biratnagar Sub-Metropolis - Jha, Kanchan; Subba, Bharat Raj (Our Nature, 2013)
Birds have always fascinated man by their exquisite coloration. They have their functional role in the ecosystem as potential pollinators and scavengers, indeed rightly called bioindicators. Nepal being a mega diversity centre harbors more than 873 species of birds which amounts to 10% of the world. Recently with increase consciousness for biodiversity census and monitoring, many new species have been added to the list. The subtropical climate and greenery of Biratnagar sub-metropolis provide good habitat for several bird species but in the past three decades drastic changes have taken place in the environment of this place because of anthropogenic activities and climate change. Several commonly visible birds’ species have left to turn out. Habitats of birds have shrunk here in such a way that very limited species of birds have become successful to show their representatives in this situation. Considering gradual loss of habitats because of increasing anthropogenic impacts and climate change, an attempt was made to study the present bird status of Biratnagar- sub metropolis. In twelve months of regular observation, eighty-one species of birds belonging to thirty-three families were recorded. Frequency of bird was counted by line transect method. The main five sites Tintolia- Balwahi (Latitude 26°26'32.4"N and Longitude 087°18'09.4"E), Baijnathpur, Ginaghat (Latitude 26029’59.8”N and Longitude 087017’53.2”E)”, Keshaliyakhola (Latitude 26°27'00"N and Longitude 087014.4’48.5”E), Dudhfarm (Latitude 26029’57.6”N and Longitude 087016’44.5”E) and Old airport (Latitude 26025’40.8”N Longitude 087016’34.3”E) were selected for study. On the basis of feeding habit birds recorded were carnivore 28.38%, omnivore 14.80%, insectivore 40.72%, fructivore 3.70%, grainivore 11.70% and nectivore 1.23%. The Shannon Wiener diversity index in summer and winter were found to be 3.68361 and 4.1328 respectively. The recorded birds were common 59.23%, fairly common 28.38% and 12.34% uncommon. The main causes of declining bird population in Biratnagar were found to have been anthropogenic impacts such as encroachment of habitats and feeding and breeding areas, use of insecticides, change in land use pattern, urbanization, poaching and effect of climate change. DOI: http://dx.doi.org/10.3126/on.v10i1.7796